Presupposition in Raya and the Last Dragon Disney animation movie (2021): A pragmatic analysis (Universitas Negeri Semarang, 2022)
Presupposition is one of phenomena in pragmatics. Before expressing their thoughts, the speakers have an assumption in their mind. This pragmatic study set out to scrutinize the kinds of presupposition in Raya and the Last Dragon movie as well as to interpret the meaning of the presupposition. Under the umbrella of descriptive qualitative method, the data were originated from Raya and the Last Dragon’s character utterances and were analyzed referring to Yule’s framework on presupposition type (1996) and language context (2006). The findings revealed that the 104 data met all six types of presupposition i.e., existential presupposition (35%), lexical presupposition (20%), factive presupposition (19%), structural presupposition (18%), counterfactual presupposition (7%) and non-factive presupposition (1%). In addition, the result indicated the use of presupposition in cinematic field presenting major descriptions for the existence of objects related to the show. Moreover, meaning of the presuppositions could be interpreted by considering the context. This study contributes to the discussion of language and its intended meaning utilized in cinematic interaction.